Employee Resilience for Organizational Development with Motivation as Mediation Variables : Mini Review - Mulyono, Sri; Perwitasari, Erni Pratiwi; Sumardi, Sumardi; Soehaditama, Josua Panatap; Susanto, Primadi Candra (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this paper is to explore the relationship between employee resilience, motivation, and organizational development in the context of private organizations, by understanding the dynamics of this relationship, it is hoped that an implementation can be found in a finding in the paper and see from these findings a literature review of effective strategies to increase employee resilience and stimulate organizational development. This paper uses a qualitative method by searching the literature for findings related to the existing papers in this paper that have been implemented in the results of existing papers. The time period of the paper is ten years.  Employee resilience has a central role in facing challenges and influencing organizational development, High motivation in employees can increase their resilience, which in turn supports organizational development. In this paper, the findings from dozens of literatures do not answer all of them, therefore links between variables are taken, and if for directly with three variables, no paper has stated the findings.